PERSEPSI DAN SIKAP ORANG TUA TENTANG TANDA GEJALA DAN PENANGANAN PERTAMA KEGAWATDARURATAN KEJANG DEMAM DAN DIARE PADA ANAK DI RUMAH - Sekarini -; Galuh Kumalasari; Ni Luh Diah Ayu Sita Dewi; Irgi Frananda Alfino (JURNAL ILMIAH KEPERAWATAN ALTRUISTIK, 2025)
Childhood is the stage of the human life cycle that is key to later life. However, at this time they are very vulnerable to illnesses that lead to fatal and dangerous conditions. This dangerous condition often occurs in the age range of infants to five years old. Of the many dangerous cases that occur, these are emergency cases that occur at home. Improper handling and assistance in emergencies when children are at home causes the child's condition to worsen and even result in death. This research method uses a quantitative descriptive research design with a cross sectional approach, namely looking at the perceptions and attitudes of parents about the signs and symptoms and the first handling of emergency cases of febrile seizures and diarrhea in children at home. The research was conducted at the Posyandu Curungrejo Village Kepanjen Malang Regency in July 2024 with a total sample of 61 people using purposive sampling technique. The sample selection criteria set were respondents who had never attended BLS/BTCLS training and the like and were not health workers (nurses and doctors). The data collection process used a questionnaire. Results: Parents' perceptions and attitudes about the signs and symptoms and the first treatment of febrile seizures and diarrhea emergencies in children at home are quite good. However, parents' perceptions on the aspects of normal temperature in children, signs of dangerous fever symptoms, the dangers of febrile seizures in children and signs of diarrhea symptoms were poor.